REMOVAL OF LEAD FROM CRUDE ANTIMONY BY USING NaPO3 AS LEAD ELIMINATION REAGENT - Ye, long-gang; Tang, chao-bo; Yang, sheng-hai; chen, yong-ming; Zhang, wen-hai (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
In order to solve the shortcomings when removing lead from crude antimony in the traditional antimony smelting, a new process was provided using NaPO3 as lead elimination reagent to yield phosphate slag, and it was removed by floating on the surface of the liquid antimony. Reaction mechanism was clarified by using the TG-DTA and XRD techniques and single factor experiments of removal lead from crude antimony were engaged. The results show that PbO and NaPO3 begin endothermic reaction at 863K (590℃), and the reaction mainly form NaPb4(PO4)3 and NaPbPO4 below 1123K (850℃) and above 1123K (850℃), respectively. Sb2O3 and NaPO3 start the reaction at 773K (500℃) and generate an antimonic salt compound. The reaction product of the mixture of PbO, Sb2O3 and NaPO3 show that NaPO3 reacted with PbO prior when NaPO3 was insufficient, amorphous antimony glass will be generated only when NaPO3 was adequate. Single factor experiments were taken with NaNO3 as oxidizing agent under argon, effect of reaction time, reaction temperature and dosage of NaPO3 and NaNO3 on smelting results. The average content of lead in refined antimony was 0.05340% and 98.85% of lead were removed under optimal conditions; the content of lead in antimony have meet the requirements of commercial antimony.